Vitamin D, cognitive function, and oxidative stress: Clues to overtraining syndrome? - Jerome, S. P. (University of Alaska, 2018)
Overtraining syndrome (OTS) is characterized by an unexplainable drop in athletic performance. It affects primarily elite, endurance athletes, though sub-elite athletes are also affected. Although the deterioration in performance is often the most pronounced and troublesome symptoms for athletes, others range from severe fatigue and insomnia to depression and lack of mental concentration. There is no known diagnostic tool except for ruling out all other possible explanations for the abnormal performance. The only known remedy for OTS is rest. Some recover within months while others take a year or more. Some athletes never fully recovery and never return to pre-OTS performance levels. The exact mechanism behind OTS is unknown. Consensus has been reached among exercise science professionals that 1) an imbalance between stress load and recovery leads to OTS; 2) OTS exists on a spectrum of possible outcomes from different exercise/rest ratios; and 3) exercise is only one part of systemic stress that can lead to OTS. In addition to physical exercise, other factors such as environmental conditions, family dynamics, schoolwork, job stressors, and social pressures all contribute to the total stress load on the body. A severe and sustained imbalance between stress and rest is a likely contributor to OTS in athletes. I investigated biomarkers and psychological markers that, in concert, could be used to identify athletes who are at the greatest risk for developing OTS before the onset of symptoms. I examined vitamin D, cognitive function, and oxidative stress status in university cross country skiers in addition to athletic performance status during the competitive ski season. This study`s results support three primary conclusions. First, collegiate endurance athletes are more prone to vitamin D insufficiency and deficiency than their sedentary counterparts. Second, collegiate cross country ski racers in the circumpolar North are unlikely to maintain adequate vitamin D during a competition season. Furthermore, vitamin D levels are likely to drop in the post-season, recovery period. Third, cognitive function is likely to be significantly higher in the post-season than during the competition season. Fourth, those who experienced a drop in performance during the competition season are more likely to show signs of oxidative stress. These findings may help to produce a screening tool for OTS.